A relevância da vontade da criança na definição do seu superior interesse - Rodrigues, Tânia Sofia Guerreiro (2021)
Over the course of the curricular internship in Barreiro’s Family and Minors Court, one of the questions that raised our interest was the intention to learn thoroughly, in what way could the child will contribute to understand and achieve their superior interest and in which ways would their participation be valued by the Court. Once defined the central guidelines of the report, we started a deep analisys of judicial proceedings - still pending or already finalised, that aproached this question. We confirmed right at the begining that the child’s will could not be analysed without studying first the definition of their best interest, as this is the foundation of everything that is a part of their life. Then, we analysed the child’s treatment evolution in the portuguese judicial system, verifying in what way did the legislator recognized autonomy to the child, so that they could develop their personality, as well as their capacities, with the purpose of becoming responsable, and sociably interventive subjects. For a better understanding of the child progressive autonomy, we analysed two complementary concepts that are fundamental for applying the child hearing and participation principle – maturity and discernment. These are established in the several analyzed legal diplomas. However, the first legal marc to foresee those was the Convention on the Rights of the Child, in its 12th article. Following this, we conducted a study on the means of the child will gauging, specially their hearing and participation, where we have done a brief legal framing on the national and international law scope. We proceeded then to theoretical-pratical appraisals, on how this principle is guaranteed in our legal order; to the changes that came from adopting the “Regime Geral do Processo Tutelar Cível” in this matter and, at last, to the consequences of the hearing deprecation. Finally, our analysis goal was to answer the question pointed above, focused on the promotion and protection procedures, in wich we presented three real cases decided by the Barreiro’s Family and Minors Court.